Blood flow-restricted resistance training modulates miRNAs to improve early hypertensive cardiac function - Zhaowen Tan; Hao Zhu; Yan Zhao; Yuchan Zheng; Jie Zhang (PLoS ONE, 2025)
Objective The aim of this study was to explore the differentially expressed miRNAs in the hearts of rats protected from early spontaneous hypertension by blood flow-restricted resistance training and to elucidate the effects of blood flow-restricted resistance training on the expression of these genes. Methods Four-week-old SHRs and WKY rats were used and randomly divided into five groups: the normal group (WKY), SHR control group (SHR-SED), high-intensity resistance training group (HIRT), medium-intensity resistance training group (MIRT), and blood flow-restricted medium-intensity resistance training group (BFRT). During the experiment, the body weight, cardiac function and hemodynamic parameters of the rats were measured. After training, total RNA was extracted from the left ventricular myocardium of rats in the SHR-SED group and the BFRT group, miRNAs were sequenced, followed by GO enrichment and KEGG pathway analyses, and the differentially expressed miRNAs were subsequently validated via qRT‒PCR. Results 1) Hemodynamic tests revealed that the blood pressure of SHRs in the BFRT decreased significantly and that the blood pressure level of SHRs in the BFRT decreased more significantly than that of the simple resistance training groups did (P < 0.05). 2) Cardiac function tests revealed that the EF, FS, and MV E/A of SHRs in the BFRT significantly increased, whereas the HR, IVSd, IVSs, LVIDd, LIVDs, LVPWd, LVPWs and LV mass significantly decreased (P < 0.05). 3) Transcriptome sequencing revealed 9 differentially expressed miRNAs in the BFRT group compared with the SHR-SED group (2 miRNAs were significantly upregulated, and 7 miRNAs were significantly downregulated), with P < 0.05 and |log2FoldChange| ≥ 1 used as the criteria for differential significance. The most prominent differentially expressed miRNA was miR-200b-3p (P = 0.00, |log2FoldChange| = 2.45). 4) The miRNA validation results revealed that BFRT significantly reduced the expression of miR-200a-3p, miR-200b-3p, miR-342-3p, miR-350, miR-429, miR-1249, miR-1949 in SHR myocardium, and increased the expression of miR-31a-5p and miR-224-5p (P < 0.01). Conclusion Eight weeks of blood flow-restricted medium-intensity resistance training could lower SHR blood pressure, and it might also improve early SHR cardiac function by regulating the expression of miR-224-5p, miR-31a-5p, miR-200b-3p, miR-200a-3p, miR-342-3p, miR-429, miR-1949, miR-1249, and miR-350, with the differential expression of miR-200b-3p being particularly significant.